Gestion d’un patrimoine, gestion d’un sanctuaire : ces femmes dont le nom s’affiche dans la cité - Marie Augier (Pallas, 2015)
The aim of this study is to analyse the visibility of Athenian women, whose name was displayed in the city in the inscriptions and shows. This analysis will bring to light the way they were identified and why they enjoyed this advertising, especially during the Hellenistic period. By reading decrees honoring priestesses and dedications and decrees containing the expression ἐκ τῶν ἰδίων, we will think about the financial autonomy of the Athenian women, when they were officials or when they made donations and consecrations.